PERSONAL EFFECTIVENESS THROUGH GRIT AND SELF-REGULATION: A GENDERIAL ANALYSIS (Forum for Linguistic Studies, 2024)
Competitive exams like the CAT require the students to be highly gritty, effective and regulated. The objective of this study is to understand the influence of gender on Grit, Self-Regulation and Personal Effectiveness. The study hypothesized that gender would play a role in development of the variables namely: Grit, Self-Regulation and Personal Effectiveness. Data was collected from 402 male and female students aged between 22 to 27 years, who are either in their undergraduate studies or in their first year of the MBA program and had taken the CAT entrance exam. Independent samples t-test results revealed a gender difference in passion dimension of Grit and stress management of personal effectiveness. The findings of the present study offer important implications to psychologists, teachers, parents, researchers, educational/coaching institutes, and majorly the students.